Bibliometric Analysis: Trends and Potential of Self-Regulated Learning (SRL) in Physics and SDGs - Rahmatta Thoriq Lintangesukmanjaya; Binar Kurnia Prahani; Dwikoranto Dwikoranto; Hidayatul Latifah; Neisya Azaria Adinda Putri (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to determine potential future research directions that can strengthen the integration between SRL and physics education in order to support the achievement of Sustainable Development Goals (SDGs), especially goal 4 on Quality Education. Method: This research was conducted using a quantitative descriptive approach, a bibliometric analysis study used data from the Scopus database to map trends and focuses on Self-Regulated Learning (SRL) research in international literature. Results: There is a global research trend in SRL and physics learning that supports the SDGs. The number of documents and citations increased from 2020 to 2025, resulting in 123 Scopus documents, with the highest number of citations in 2024, reaching 185. Novelty: The findings of the bibliometric analysis identified three main aspects of SRL research on physics materials and their influence on the SDGs, including the use of AI technology, relevant learning models, and learning processes. Future research directions hold great potential for integrating technologies such as AI and IoT devices into SRL to support the achievement of the Sustainable Development Goals (SDGs). This finding is in innovative learning planning focused on self-satisfaction in the era of technology adoption.